A sociological analysis of Rhodes University students' understanding of depression - Kadula, Tadala (Rhodes University, Faculty of Humanities, Department of Sociology, 2019)
Using the theoretical framework of symbolic interactionism, this research sought to analyse and explore how Rhodes University students, both depressed and not depressed, understand depression, and how their understanding influences their interaction with people who do suffer from depression. For the purposes of this paper, eight participants were involved in an in-depth interview process. Out of the eight participants, six of them suffered from depression while the other remaining two participants had never suffered from depression, but they were close to someone who had depression. The findings of this research varied, some understood depression as a mental disturbance, others understood it as a condition that affects your emotions, and others understood it as a multifaceted condition that is highly subjective and cannot be understood using standardized measures. The participants' personal experience and introduction into a new environment, in this context, university, changed their understanding of depression. The change in how they understood depression correlated with the change in how they interacted with depressed people.
Keywords: College students -- South Africa -- Mental health; College students -- South Africa -- Mental health -- Case studies; Depression, Mental; Rhodes University -- Students -- Attitudes